Can mass fundraising harm your core business? A field experiment on how fundraising affects ticket sales - Maja Adena; Steffen Huck (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
Some companies engage in mass fundraising in addition to their core business. Via a corporate social responsibility (CSR) channel this may increase sales. However, ask avoidance, if present, could imply that fundraising activities may harm a company's core business. We examine how asking for donations affects ticket sales of a publicly owned leading opera company. In two large-scale randomized controlled trials with over 50,000 opera visitors, who are asked to donate for an opera-organized social youth project, we find that donations can crowd out ticket expenditure during a campaign. But for the longer run we observe a precisely estimated null effect.
Keywords: C93; D64; D12; L21; M14; 330; Charitable giving; field experiments; ask avoidance; corporate social responsibility